Prevalence Of Unintended Pregnancy Among Female Adolescents In Anambra State: Its Risk And Protective Factors - Okechukwu Aleke, Christian; Eni Eluu, Patrick; Okereke Olom, Michael; N. Afoke, Eunice; Nwankwo, Chinedu; Chisom Igwe, Basil; Anulika Ogbu, Joy; Mercy Eberechi, Ugbor-Aku; God’slove Oko, Omaka; Anulika Alo, Joy; E. Obinma, Chidnma (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Pregnancy is usually a God blessings and welcome development when it occurs at the appropriate time during wedlock and among couples in marriage. On the contrary, it may trigger a serious health, social and economic consequences if it occurs unintended, outside of wedlock or during the adolescent’s secondary schools. The study explored prevalence of unintended pregnancy among female adolescents in Anambra State: Its Risk and Protective Factors. This was cross-sectional quantitative survey research design conducted among 240 female adolescents/adults in Anambra state. A semi structured questionnaire using purposive/ convenience sampling was the instrument and sampling method used for data collection. The analysis of data was done using mean (x) and standard deviation to answer the research questions, and t-test statistics to test the hypothesis at 0.05 level of significance. The results shows that the prevalence of unintended pregnancy was 12.0%. Poverty level (3.70), Pressure from peers to have sex” (3.60), Poor parental supervision (2.09) were the risk factors. The protective factors amongst others were that parents should be educated through seminars on the importance of discussing sexuality and the dangers of premarital sex with their children especially the females (98.3%). The findings underscore the need for proper education and parental intervention of the female adolescents and as well increased awareness on the use of contraceptive, so as to bridge the large gap of unmet need.